FIELD CONTROL EFFECT OF 10 INSECTICIDES ON BEMISIA TABACI IN GREENHOUSE TOMATOES IN CHINA - Шунсяо, Лю; Власенко, В. А. (Bulletin of Sumy National Agrarian University. The series: Agronomy and Biology, 2022)
Bemisia tabaci (tobacco whitefly) is one of the most harmful invasive species in the world. It causes devastating damage to many crops during the invasion process and is an important pest worldwide. B. tabaci harms crops mainly by directly feeding on plant juice, affecting plant nutrient metabolism, causing plant leaves to appear yellow spots, yellowing and falling off in severe cases, and abnormal or irregular fruit structure. Adults and nymphs of B. tabaci can also secrete honeydew to contaminate plant organs and induce coal pollution. When the density is high, the leaves can turn black, which seriously affects the photosynthesis of plants and reduces the quality of crops. Another important way of B. tabaci is to spread plant viruses. Generally, after an outbreak of B. tabaci, the virus transmitted by it will occur. These viruses can cause plant leaf curling, plant dwarfing and fruit abortion, causing serious losses. A single foliar spray of 10 pesticides was used in order to screen out high-efficiency pesticides for controlling B. tabaci on tomato. Control experiments to carry out at the initial stage of the occurrence of B. tabaci, and a survey of the control effect was carried out 1, 3 and 7 days after the treatment. The results showed that the best effect on B. tabaci had on F (5 % Diprofen) variant 1 day after treatment. It was 41 %, which was significantly higher than other test reagents. None of the reagents showed good fast-acting effects. Option C (22,4 % Spirotetramat) had the best control effect on B. tabaci three days after spraying – 72 %. The worst effect (62 %) was when treated with pesticides in experimental variants I (50 % Flonicamid) and G (10 % Cyantraniliprole). Spraying the plants gives the best effect of neutralizing the pest and is 86 % on option J (20 % Mevirpirazone) after 7 days, which is much higher than other test reagents. Phytotoxicity for tomatoes was not detected in three field studies conducted from 13 to 20 October 2020. We can choose in the field control process of pest B. tabaci 20 % Mevirpirazone suspension concentrate, which can be used in combination with 22,4 % Spirotetramat suspension concentrate and 5 % Diprofen dispersible concentrate to achieve better control effect. This method of pesticides selection will provide effective protection of greenhouse vegetables from the damage impact of pest B. tabaci.